(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2016)
Art is often isolated in our society. People rarely realize its importance and value. I have come across with different periphery of communities after the big roar of the nature. More than nine thousand people have died, millions homeless, billions of properties got destroyed and traumatized the souls of the nation. It became the national and international concern just because it hit the important cities and world heritage sites of Nepal. Major art and artifacts got broken and many of our cultural heritage sites are still in the verge of ruin. Though people feel the loss, Art is still not in the priority.